2019
DOI: 10.3390/jcm8101603
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-Mesenchymal Transition-Related MicroRNAs and Their Target Genes in Colorectal Cancerogenesis

Abstract: MicroRNAs of the miR-200 family have been shown experimentally to regulate epithelial-mesenchymal transition (EMT). Although EMT is the postulated mechanism of development and progression of colorectal cancer (CRC), there are still limited and controversial data on expression of miR-200 family and their target genes during CRC cancerogenesis. Our study included formalin-fixed paraffin-embedded biopsy samples of 40 patients (10 adenomas and 30 cases of CRC with corresponding normal mucosa). Expression of miR-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…At the invasive tumor front, TGFB2 was the only gene with inverse expression to the miR-200 family. This is in accordance with our previous study demonstrating a negative correlation between TGFB2 and three of five members of the miR-200 family , namely miR-200a , miR-200c and miR-141 , in CRC with lymph node metastases ( 19 ). Increased expression of TGFB2 mRNAs and protein has also been reported in CRC progression ( 38 , 39 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…At the invasive tumor front, TGFB2 was the only gene with inverse expression to the miR-200 family. This is in accordance with our previous study demonstrating a negative correlation between TGFB2 and three of five members of the miR-200 family , namely miR-200a , miR-200c and miR-141 , in CRC with lymph node metastases ( 19 ). Increased expression of TGFB2 mRNAs and protein has also been reported in CRC progression ( 38 , 39 ).…”
Section: Discussionsupporting
confidence: 94%
“…All of the samples included in the study had passed this initial quality control and those that did not amplify were not included in the study. Positive and negative amplification of RNU6B was in 100% correlation with positive and negative amplification of GAPDH (100 bp) used as initially quality control in previous research (data not shown) (19,30). For selected genes, we chose TaqMan primers and probes that amplify and detect PCR products less than 100 bp long (Table 1).…”
Section: Rna Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PTPN13 might hinder EMT also through cell junction stabilization via its positive role on desmosome formation, as demonstrated in vitro in MDA-MB-231 breast cancer cells that overexpress PTPN13 and in vivo in a transgenic mouse model that lacks PTPN13 [ 53 ]. Although inhibition of miRNA-200c, which targets PTPN13, is associated with EMT [ 33 ], an in vivo study found no significant association between downregulation of the miRNA-200 family, PTPN13 expression, and colorectal cancer metastatic potential [ 91 ].…”
Section: Signaling Pathways and Biological Activities Affected By mentioning
confidence: 99%
“…In this Special Issue, the authors discuss the implications of the EMP seen in stemness, drug resistance [ 6 ], immune-suppression [ 7 , 8 , 9 ], metabolic reprograming and the interaction of cancer cells with the tumor microenvironment. We have diverse topics related to the transcriptional and microRNA-mediated control of EMP networks [ 10 , 11 ], the multi-omics [ 12 , 13 ] and morphological mapping of EMP [ 14 ], integrative approaches to link EMP with metabolic reprogramming and/or autophagy [ 15 , 16 ], and the designing of novel ex vivo systems such as microfluidic setups and 3D polymer scaffolds to visualize the dynamics and heterogeneity of EMP in cancer cells [ 17 , 18 ]. This Special Issue, through a collection of review and research articles, represents the emerging inter-disciplinary approaches being taken to elucidate the nonlinear dynamics of EMP and their differential contributions to disease aggressiveness.…”
mentioning
confidence: 99%